1997
DOI: 10.1038/nm0397-306
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adeno-associated virus for muscle directed gene therapy

Abstract: Although gene transfer with adeno-associated virus (AAV) vectors has typically been low, transduction can be enhanced in the presence of adenovirus gene products through the formation of double stranded, non-integrated AAV genomes. We describe the unexpected finding of high level and stable transgene expression in mice following intramuscular injection of purified recombinant AAV (rAAV). The rAAV genome is efficiently incorporated into nuclei of differentiated muscle fibers where it persists as head-to-tail co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
428
3
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(460 citation statements)
references
References 32 publications
26
428
3
1
Order By: Relevance
“…18,41 Skeletal muscle in particular has been used successfully for long -term expression of transgenes by rAAV. 21,30,42,43 When this approach was taken in the present investigation, it was observed that a single intramuscular injection of the rAAVHuEndo vector could lead to elevated serum endostatin levels by 4 weeks after injection (Fig 7 ). The endostatin levels reached a plateau value by 6 to 8 weeks (Fig 7) and were maintained as long as 4 months after injection.…”
Section: Discussionmentioning
confidence: 79%
“…18,41 Skeletal muscle in particular has been used successfully for long -term expression of transgenes by rAAV. 21,30,42,43 When this approach was taken in the present investigation, it was observed that a single intramuscular injection of the rAAVHuEndo vector could lead to elevated serum endostatin levels by 4 weeks after injection (Fig 7 ). The endostatin levels reached a plateau value by 6 to 8 weeks (Fig 7) and were maintained as long as 4 months after injection.…”
Section: Discussionmentioning
confidence: 79%
“…[5][6][7][8][9] Intramuscular (IM) injection is a convenient method owing to physical accessibility, mass of the tissue and access to the vasculature. [10][11][12] Moreover, recombinant adeno-associated viral (rAAV) vectors and naked plasmid are two different gene transfer systems used for IM delivery in animal models [13][14][15][16][17] and in humans. 18,19 Recently, regional vascular infusion of a vector to achieve skeletal muscle transduction has been reported for plasmid DNA (pDNA) 20,21 and for rAAV vectors.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of pilot studies the lacZ gene delivered by an AAV vector has been shown to make active ␤-galactosidase in cultured cells and animal tissues. [18][19][20][21] In treated muscle of immunocompetent mice, this expression was shown to persist for 1.5 years. 19 Potentially therapeutic proteins that have been shown to be delivered and expressed by AAV vectors include erythropoietin, 20 cystic fibrosis transmembrane conductance regulator, 22 blood coagulation factor IX, 23,24 and GUS.…”
Section: Introductionmentioning
confidence: 99%
“…19 Potentially therapeutic proteins that have been shown to be delivered and expressed by AAV vectors include erythropoietin, 20 cystic fibrosis transmembrane conductance regulator, 22 blood coagulation factor IX, 23,24 and GUS. 21 In none of these cases, however, were experiments designed to show that the AAV-mediated gene therapy actually affected the long-term course of a disease. Results presented here show that MPS VII mice treated with an AAV vector containing mouse GUS cDNA (AAV-GUS) acquire the ability to make GUS enzyme for an extended period of time.…”
Section: Introductionmentioning
confidence: 99%